Comparison of increased overjet cases and controls: normative data for condylar positions - BİREN, SİBEL (WILEY, 2007)
The aim was to compare normal overjet versus large overjet cases with clinically healthy temporomandibular joints (TMJ); to establish normative data regarding the difference between condylar positions in centric occlusion (CO) and maximum intercuspation (MI) and deflective CO contacts. Two study groups of normal overjet and large overjet cases consisted each of 33 subjects with no detectable clinical signs of temporomandibular disorder (TMD). CO-MI differences were recorded using the SAM(R) Mandibular Position Indicator. Deflective contacts were examined on models mounted in CO. There was a significant difference between groups in the vertical (P = 0.030) and transverse (P = 0.008) range of movement from CO to MI, but not in the antero-posterior direction. There were no differences in the location of deflective contacts. Results of this study showed that patients with increased overjet show some differences compared with normal overjet patients, even in the non-patients. Further research on TMD patients is needed to find out about the role these features play in the aetiology and treatment of temporomandibular disorder (TMD). This study indicates that the clinician should be paying special attention to the TMJ status of patients with a large overjet.
Keywords: overjet; centric occlusion; maximum intercuspation; deflective contacts; mandibular position indicator; TEMPOROMANDIBULAR DISORDERS; OCCLUSAL VARIABLES; CENTRIC RELATION; YOUNG-ADULTS; DYSFUNCTION; SYMPTOMS; SIGNS; MALOCCLUSION; OVERBITE; CHILDREN